Gambaran Pengetahuan dan Sikap Keluarga Pasien Tentang Penularan Tuberkulosis di Ruangan Tulip RSUD Syekh Yusuf Gowa - Sri Yulil Asmi; Andi Budiyanto Adi Putra; Asriani Bahar; Sennahati Sennahati (Fatiakara Care: Jurnal Ilmiah Keperawatan, 2026)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis and remains a major public health concern in Indonesia. Its airborne transmission places family members of patients at high risk, especially when their knowledge and attitudes toward prevention are lacking. This study aims to describe the knowledge and attitudes of patients’ families regarding TB transmission in the Tulip ward of Syekh Yusuf Regional Hospital, Gowa.This research employed a quantitative approach with a descriptive design. The sample consisted of 30 family members selected using accidental sampling. A closed-ended questionnaire was used to assess respondents' knowledge and attitudes. Data were analyzed descriptively and presented in frequency distributions and percentages.The results showed that the majority of respondents had good knowledge (23 people or 77%), moderate knowledge (7 people or 23%), and none had poor knowledge. Meanwhile, attitudes toward TB transmission prevention were predominantly good (18 people or 60%), moderate (11 people or 37%), and only 1 person (3%) had a poor attitude. Most respondents were female (60%) and aged between 25–33 years (43%). It can be concluded that most family members of TB patients at Syekh Yusuf Regional Hospital have good knowledge and attitudes regarding TB transmission. This highlights the importance of health education provided by healthcare workers to patient families in order to enhance understanding and active participation in TB prevention efforts.